Karakter Morfologi dan Nutrisi Genotipe Talas Mapia di Distrik Supiori Utara dan Timur Kabupaten Supiori Provinsi Papua - Benti Purba; Saraswati Prabawardani; Wasgito Purnomo; Yohanis Amos Mustamu (Program Pascasarjana Universitas Papua, 2022)
This study aimed to identify morphological characters and analyze the nutrition of the Mapia taro genotype and other taro genotypes in Kpudori and Warbor villages in North Supiori district and Wakre and Wafor villages in East Supiori district. The research was conducted in June – August 2020 using a descriptive method with survey techniques. Chemical analysis of tubers was carried out at the Agroclimatology Laboratory, Faculty of Agriculture, University of Papua and the Laboratory of Chemistry and Food Technology, Research Institute for Nuts and Tubers, Malang. In this method, taro samples were taken from a population of taro plants in a predetermined village in each of the North and East Supiori districts. The sampling method for morphological characterization was carried out randomly on 3 taro plants per village. Observations on plant morphological characteristics (above gound plant part) were carried out on taro plants aged approximately 90-150 days after planting (DAT). While the morphological characterization of tubers was carried out at harvest. The standardized qualitative and quantitative data were processed using the SPSS program with cluster analysis to determine the level of similarity between the genotypes of each sample of each taro. Cluster analysis produced a dendogram which was used to assess the level of similarity of the taro genotypes from the data obtained. The results showed that the highest association coefficient values were found in the KDR-TP and KDR-IU genotypes of 11.044. This shows that the two genotypes have a low level of similarity compared to other taro genotypes. While the lowest coefficient value was found in the WKR-TP and WFR-TP genotypes with a coefficient value of 4.064, indicating that the WKR-TP and WFR-TP accessions had a high degree of similarity. The results of the chemical analysis of tubers varied in 6 genotypes of taro. The highest water content was WBR-TP genotype (87.88%), ash content (4.59%) in WFR-TP genotype, starch content (67.24%) in WKR-IP genotype, sugar content (11 0.01%) in KFR-IU, amylose content (22.91%) in WBR-TP, fat content (0.64%) in KDR-IU, protein content (8.81%) in WFR-TP.